Kolaborasi Edukatif Orang Tua dan Sekolah sebagai Strategi Pembentukan Karakter dan Akhlak Mulia Anak Usia Sekolah Dasar - Viki Bayu Mahendra; Ghufron Ali Sya’bana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This community service program was initiated in response to the need to strengthen collaboration between parents and schools in fostering character development and noble morals among elementary school students. The main issue addressed was the lack of structured and sustainable educational collaboration between parents and the school in supporting character-building practices. The program aimed to develop a participatory and reflective collaboration model through a systematic parenting initiative. A qualitative participatory approach based on community engagement was employed, consisting of needs assessment, joint discussion and planning, parenting program design, workshops and Focus Group Discussions (FGDs), mentoring and monitoring, as well as evaluation and reflection. The results highlight significant improvements in two-way communication between parents and teachers, increased collective awareness of the family’s strategic role in character education, and the establishment of a regular communication forum as a new social structure within the school community. Positive changes were also observed in parenting practices, including the implementation of positive discipline and empathetic communication at home aligned with school values. The emergence of local parent leaders further strengthened program sustainability. Overall, the participatory educational collaboration model proved effective in promoting social transformation and reinforcing sustainable character and moral development among students.